Dynamic Mechanical Response of Biomedical 316L Stainless Steel as Function of Strain Rate and Temperature - Woei-Shyan Lee; Tao-Hsing Chen; Chi-Feng Lin; Wen-Zhen Luo (Bioinorganic Chemistry and Applications)
A split Hopkinson pressure bar is used to investigate the dynamic mechanical properties of biomedical 316L stainless steel under strain rates ranging from 1 × 103 s-1 to 5 × 103 s-1 and temperatures between 25∘C and 800∘C. The results indicate that the flow stress, work-hardening rate, strain rate sensitivity, and thermal activation energy are all significantly dependent on the strain, strain rate, and temperature. For a constant temperature, the flow stress, work-hardening rate, and strain rate sensitivity increase with increasing strain rate, while the thermal activation energy decreases. Catastrophic failure occurs only for the specimens deformed at a strain rate of 5 × 103 s-1 and temperatures of 25∘C or 200∘C. Scanning electron microscopy observations show that the specimens fracture in a ductile shear mode. Optical microscopy analyses reveal that the number of slip bands within the grains increases with an increasing strain rate. Moreover, a dynamic recrystallisation of the deformed microstructure is observed in the specimens tested at the highest temperature of 800∘C.